2022
DOI: 10.1111/jocs.16477
|View full text |Cite
|
Sign up to set email alerts
|

Mitral valve repair versus replacement in severe ischemic mitral regurgitation systematic review and meta‐analysis

Abstract: Background and Aim Ischemic mitral regurgitation (IMR) is a serious consequence of coronary artery disease. The choice of the optimal surgical strategy remains debatable. The aim of the present meta‐analysis is to compare the outcomes of mitral valve repair (RPR) versus replacement (RPL) regarding perioperative mortality, overall mortality, reoperation, recurrence of MR, and reverse remodeling after surgery. Methods Electronic searches were performed using the searchable databases of Google Scholar, Pubmed, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…We believe it is time to end this feud between repair and replacement (Figure 1). It is now obvious that they are both worthwhile surgical approaches, and this is also confirmed by the meta‐analysis by Gamal et al 6 …”
Section: Figurementioning
confidence: 64%
See 2 more Smart Citations
“…We believe it is time to end this feud between repair and replacement (Figure 1). It is now obvious that they are both worthwhile surgical approaches, and this is also confirmed by the meta‐analysis by Gamal et al 6 …”
Section: Figurementioning
confidence: 64%
“…10 We believe it is time to end this feud between repair and replacement (Figure 1). It is now obvious that they are both worthwhile surgical approaches, and this is also confirmed by the meta-analysis by Gamal et al 6 Already at the beginning of the 2000s, we proposed a simple echocardiographic parameter, the coaptation depth, to choose between the two techniques, reserving replacement for patients with worse LV remodeling, going against the dogma according to which MV repair should be the predominant choice to be adopted. 11 Today we know that isolated annuloplasty may not be enough to reach a long-term stability and competence of the valve and, in these cases, we can choose between a more complex MV repair procedure that includes also a valvular and subvalvular procedure, or valve replacement.…”
mentioning
confidence: 76%
See 1 more Smart Citation
“…4 There is a preponderance of evidence that mitral valve repair is associated with improved outcomes over valve replacement, including decreased risk of mortality and device infection, and no requirement for postoperative anticoagulation. 5,6 Despite the overwhelming evidence in favor of repair for primary mitral disease, a significant variability in repair rates among surgeons and hospitals remains. [7][8][9] Analysis of practice patterns in New York revealed that repair rates varied from 48% to 77% and were directly related to annual surgeon volume.…”
Section: Introductionmentioning
confidence: 99%
“…4 There is a preponderance of evidence that mitral valve repair is associated with improved outcomes over valve replacement, including decreased risk of mortality and device infection, and no requirement for postoperative anticoagulation. 5,6…”
Section: Introductionmentioning
confidence: 99%